The Correlation Between Reflection on Action and Academic Burnout in Nursing Professional Students - Evrilia Sabella Fatikha; Iyos Sutresna; Heri Ridwan (Jurnal Vocational Nursing Sciences (VNUS), 2026)
Nursing professional education represents a transitional period from academic learning to clinical practice, The high academic and clinical demands place students under significant pressure, increasing the risk of academic burnout. Addressing academic burnout requires effective coping strategies, including reflective practices such as reflection on action. This study aimed to determine the level of reflection on action, the level of academic burnout, and the relationship between the two variabels. A quantitative method with a descriptive correlational approach was used. Data were analyzed using univariate analysis and Pearson correlation, as the data were normally distributed. The results showed that both reflection on action and academic burnout were at a moderate level. A significant negative correlation was found between reflection on action and academic burnout (p = 0.005; r = -0.378). This indicates that higher levels of reflection on action are associated with lower levels of academic burnout among students. Future studies are recommended to include larger sample sizes and more comprehensive research design.